1996
DOI: 10.1097/00005053-199601000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Psychiatric Disorders in Medical Inpatients

Abstract: The aim of the present study was to determine the prevalence of psychiatric disorders in acutely ill medical inpatients. A total of 313 consecutively admitted patients were interviewed using a semistructured psychiatric interview. Diagnoses were made according to DSM-IV diagnostic criteria during two time periods, the 7 days following admission and the month prior to admission. The results showed that 85 patients (27.2%) received a DSM-IV diagnosis, with several patients having comorbid diagnoses. Major depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0
15

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(97 citation statements)
references
References 57 publications
6
76
0
15
Order By: Relevance
“…For example, a primary diagnosis of mental and behavioral disorders due to the use of psychoactive substances (F10-19) was infrequent (7%) in this population compared with the 30% prevalence rate found by some authors [27,28], although it is comparable with the results obtained by others (e.g., 5.4%) [29]. This may be due to the fact that specific psychiatric services for individuals with these disorders were set up after the psychiatric reform in Italy and therefore such patients are usually referred to these services rather than to C-L.…”
Section: Discussionsupporting
confidence: 82%
“…For example, a primary diagnosis of mental and behavioral disorders due to the use of psychoactive substances (F10-19) was infrequent (7%) in this population compared with the 30% prevalence rate found by some authors [27,28], although it is comparable with the results obtained by others (e.g., 5.4%) [29]. This may be due to the fact that specific psychiatric services for individuals with these disorders were set up after the psychiatric reform in Italy and therefore such patients are usually referred to these services rather than to C-L.…”
Section: Discussionsupporting
confidence: 82%
“…Among specific medical groups, studies have demonstrated that AD was almost three times as common as major depression (13.7 versus 5.1%) in acutely ill medical inpatients 22 and was diagnosed in 35% of cancer patients experiencing a recurrence 23 . In obstetric/gynaecology consultation-liaison, 24 adjustment disorders predominated over mood disorders.…”
Section: Consultation Liaison Psychiatrymentioning
confidence: 99%
“…[1][2][3][4][5] Major depression is among the most frequently observed psychiatric comorbidities seen in medical patients, and its presence is specifically associated with poor outcomes. Major depression is highly prevalent in physically ill patients, 6 and it affects quality of life and course of the somatic illness.…”
Section: Prevention Of Major Depression In Complexmentioning
confidence: 99%